On the Role of Teacher–Student Rapport and Teacher Support as Predictors of Chinese EFL Students’ Affective Learning - Sun, Yuchao; Shi, Wenshu (Frontiers in Psychology, 2022)
Students’ affective learning is critical for their academic success; therefore, considerable attention has been devoted to the role of various student-related and teacher-related factors as predictors of student affective learning. Notwithstanding, the impact of two important teacher-related factors, namely teacher-student rapport and teacher support, has not been adequately researched. To address this gap, the present study sought to explore the role of teacher support and teacher-student rapport in Chinese English as a foreign language (EFL) students’ affective learning. To do so, three valid inventories of the variables were administered to 497 Chinese EFL students. Performing correlational analyses, favorable associations were found between teacher-student rapport, teacher support, and student affective learning. The predictive power of teacher support and teacher-student rapport was assessed using structural equation modeling (SEM). Chinese EFL students’ affective learning was shown to be largely influenced by teacher-student rapport and teacher support. The pedagogical implications and future directions are also discussed.